Voices from the future: A Qualitative exploration of undergraduate nursing students' perspectives on the nursing profession - Khalaf Attia, Younes; Salih, Mohammed; Abd Ahmed, Atheer; Karam Yaseen Fathi (KHD-Production, 2025)
The nursing profession is one of the most important in providing health care; therefore, understanding the attitudes of undergraduate nursing students is imperative. This understanding aids in recruiting, teaching, and mentoring future nurses in the best ways possible. The primary aim of this research was to assess the perception of undergraduate nursing students regarding the nursing profession at Mosul University. A qualitative phenomenological design was done between December 12, 2023, and February 25, 2024. The study employed a qualitative research design in which a proportional purposive sampling procedure, group and individual interviews, and thematic analysis were used in data collection and analysis. In choosing participants for the study, a purposive sampling technique was used in-house, emphasizing undergraduate nursing students at Mosul University. Five open-ended questions were posed to the twenty-five participants, and the questions were aimed at unraveling the participants' views, expectations, and opinions about the nursing profession. The interviews were tape-recorded, and the responses obtained were transcribed verbatim, and themed analysis was conducted. From the study, it can be deduced that students have a favorable attitude towards the nursing profession. Some view nursing as a fulfilling and meaningful employment driven by their desire to help people in need. Nevertheless, some issues are connected with the challenges and tasks inherent in the profession. Therefore, there are other social and cultural factors that influence nursing students' attitudes, some of which include societal beliefs about the profession or stereotypes. Nursing as a profession is usually accompanied by the aim of caring for and improving the quality of life of other people. It consists of patience, taking the side of the patient, and the need to support this patient in enhancing their health. Emphasis is placed on interpersonal communication, interpersonal relations, teamwork, principles of justice and equity, and the overall well-being of each client. Nursing is a relatively safe and provided profession because of the continually increasing need for nurses, but the job is not easy, and people need help in managing the load and combating burnout.